Duffy's Iowa Caucus Cartoons : Watch 'Em Run - Duffy, Brian, 1955- (Book collections on Project MUSE., 2016)
"Brian Duffy has been poking fun at the Iowa caucuses for just about as long as they've been a media circus, since the 1970s. Now, the longtime editorial cartoonist has gathered a selection of his best images lampooning the politicians on their quadrennial stampedes through Iowa's fields and towns. Whether you're anticipating or dreading the onset of another caucus season in 2016, this book will put it all into perspective. From Jimmy Carter's innovative 1976 effort to Barack Obama's come-from-behind win in 2008, from George H. W. Bush's storming to victory in 1980 to George W. Bush's coasting to his win in 2000, from Gary Hart's peccadillos in 1988 to John Edwards's missteps in 2008, from Elizabeth Dole's determination to breach the White House boys' club in 2000 to Hillary Clinton's fall from frontrunner to third place in 2008, here is American presidential campaigning in all its glory. With pigs. "--